Morphological and Syntactic Bases of Arabic Dictation Rules - Mohammad Ahmad Abu Eid (دراسات في اللغة العربيّة وآدابها)
Â  This study aims at examining the morphological and syntactic bases of Arabic spelling rules. It describes the state of Arabic script before the authorization of the present dictation rules and the resulting state of Arabic spelling after the rules were laid down . It also aims at investigating the attempts writing and spelling experts make to establish specific writing forms which accord with both morphological or grammatical features and properties of the items. The study concludes that many spelling rules have been established because the experts have considered the morphological and grammatical of the words concerned. The article also provides textual examples in all cases.